Inverse Problems for Sturm-Liouville-Type Differential Equation With the Fixed Delay Under Discontinuity Conditions - Bošković, Milica; Vladičić, Vladimir (Sarajevo Journal of Mathematics, 2022)
In this manuscript, we consider boundary value problems for the equation with the fixed delay and transmission conditions on $\frac{π}{2}$. We study the case when all parameters in transmission conditions are known. We will prove theorem of uniqueness from two spectra, first with Dirichlet-Dirichlet boundary conditions and second with Dirichlet-Neumann boundary condition. Also, we implicitly give the algorithm for determining the potential from these two spectra.